2017
DOI: 10.1016/j.ejvs.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistulae for Haemodialysis: A Systematic Review and Meta-analysis of Efficacy and Safety Outcomes

Abstract: Reported fistula patency rates may overstate their potential clinical utility when time to maturation, maturation rate, abandonment and infection are considered. Protracted maturation times, abandonment and infection all have a significant impact on evaluating the clinical utility of fistula creation. A rigorous and consistent set of outcomes definitions for hemodialysis access are necessary to clarify factors contributing to fistula success and the clinical consequence of fistula failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
123
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 21 publications
6
123
0
2
Order By: Relevance
“…Although the time to maturation was shorter among AVG than AVF, both access types had similar rates of maturation and sustained access use. We found that 25% of AVF were abandoned without use, which is comparable to the rate of 21% described in our previously reported meta-analysis [7]. Interestingly, the median time of access use was similar between both access types, with a median of 8 months for AVF and 7 months for AVG.…”
Section: Doi: 101159/000495355supporting
confidence: 70%
See 2 more Smart Citations
“…Although the time to maturation was shorter among AVG than AVF, both access types had similar rates of maturation and sustained access use. We found that 25% of AVF were abandoned without use, which is comparable to the rate of 21% described in our previously reported meta-analysis [7]. Interestingly, the median time of access use was similar between both access types, with a median of 8 months for AVF and 7 months for AVG.…”
Section: Doi: 101159/000495355supporting
confidence: 70%
“…Interestingly, the median time of access use was similar between both access types, with a median of 8 months for AVF and 7 months for AVG. Our follow-up period was not sufficient for a full analysis of patency, as the mean patency of AVF is around 28 months [7] and the median follow-up time in this cohort was 13 months (range 1-32).…”
Section: Doi: 101159/000495355mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis reported a growing percentage of patients with non-functioning AVFs because of maturation failure in recent decades. 11 This observation might be largely a result of a change in patient demographics, with advanced age, diabetes mellitus, and nephrosclerosis as leading causes of ESRD. In these patients, calcified and noncompliant arteries and sclerotic veins might be responsible for failed vessel adaptation, resulting in low arteriovenous (AV) bloodflow and impaired vessel diameter increase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AVF failure is also a major issue of vascular access related to the HD. A recent study demonstrated that the primary and secondary patency of AVFs at one year were only 64% and 79% [ 11], which further confirms the importance of intensive examinations for the early detection of clarifying risk factors to prevent the occurrence of AVF failure. However, to date most of the studies about the risk factors for AVF failure were still controversial [ 12,13].…”
mentioning
confidence: 79%